1991
DOI: 10.1111/j.1532-5415.1991.tb04052.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Markers of Alzheimer's Disease

Abstract: Objective: To review studies on cerebrospinal fluid (CSF) in patients with Alzheimer's disease (AD) in order to answer the question whether CSF contains a specific marker which can be used to support a clinical diagnosis of AD. Data sources: Studies identified through an English‐language literature search using MEDLINE (1966 to 1990) and a review of bibliographies of relevant articles. Study Selection: All studies on CSF in AD patients were selected. Double publications on the same original data were not inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 168 publications
0
4
0
Order By: Relevance
“…For the antioxidant glutathione (GSH), 13 publications were rejected [ 35 - 47 ]. For the amino acids, 20 publications were rejected [ 41 , 48 - 67 ]. Last, for the metabolites/neurotransmitters 14 publications were rejected [ 5 , 58 , 68 - 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the antioxidant glutathione (GSH), 13 publications were rejected [ 35 - 47 ]. For the amino acids, 20 publications were rejected [ 41 , 48 - 67 ]. Last, for the metabolites/neurotransmitters 14 publications were rejected [ 5 , 58 , 68 - 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Until the identi¢cation of tau and Ab 42 proteins in CSF, these attempts were destined for the dustbin. 114 However, the many studies aimed at quanti¢cation of both tau and Ab 42 in CSF have demonstrated that their analysis may contribute to the di¡erential diagnostic work-up of dementia syndromes, especially in the identi¢cation of AD patients. Recommendations made by an international consensus group state that the sensitivity for the ideal AD biomarker should exceed 80% with a speci¢city of distinguishing other dementia syndromes of more than 80% as well.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have focused on the cerebrospinal fluid (CSF) for the presence ofa biochemical change that may be a diagnostic marker for AD (reviewed in ref. 3). Amyloid, paired helical filament, and a1-antichymotrypsin immunoreactivity have been reported to be elevated in the CSF of AD patients (4)(5)(6).…”
mentioning
confidence: 99%